Assessment of Intravenous Antibiotics to Peroral Antibiotics Conversion Practice and Its Associated Factor at University of Gondar Comprehensive Specialized Hospital: Prospective Observational Study - Getachew Yitayew Tarekegn; Samuel Berihun Dagnew; Samuel Agegnew Wondm; Bekalu Kebede; Emneteab Mesfin Ayele (Canadian Journal of Infectious Diseases and Medical Microbiology, 2022)
Background. Improper utilization of antibiotics harms the patient, the public, and the economy. The overuse of injections is one of the key factors in the irrational use of medicines. However, little is known about intravenous (IV) to peroral (PO) conversion practice in the Ethiopian healthcare setting, specifically in the Northwest part of Ethiopia. Objective. To assess antibiotics IV to PO conversion practice and its associated factors at the internal medicine ward of the University of Gondar Comprehensive and Specialized Hospital (UOGCSH). Method. A prospective observational study was conducted on 324 study participants who were admitted to the University of Gondar Specialized Hospital from October 3 to November 14, 2021. A systematic random sampling technique was employed to select the study participants. Stata version 14.2 was used for the analysis. Descriptive statistics result was presented using mean and standard deviation. Logistic regression analysis was done to determine the association between independent variables and dependent variables. The association between independent variables and dependent variables was tested at 95% CI and P value≤ 0.05 was considered statistical significance. Result. A total of 324 study participants were included in the study, and the mean age of the patients was 41.4 ± 18.6. Of the 324 study participants, 63.3% were male. The most frequently prescribed antibiotics used for empiric treatment were ceftriaxone (45.4%), followed by metronidazole (33.2%), and cloxacillin (11.4%). A total of 34.5.57% of patients who took antibiotics were converted to PO antibiotics. The most frequently converted type of conversion practice was sequential (23.1%), followed by the switch type of conversion (7.4%). Tachypnea, unavailability of medication, higher temperature, hospital stay greater than 10.78-days, and the presence of comorbidity were predictors of IV medications not being converted to PO medications. Conclusion. Intravenous to peroral conversion practice was infrequent. The most frequently applied conversion practice was sequential type conversion practice, followed by switch type of conversion practice. IV to PO conversion practice was significantly associated with tachypnea, unavailability of medication, higher temperature, hospital stay greater than 10.78-days, and comorbidity. Awareness of IV to PO conversion practice and short-term training for healthcare teams is vital for better antibiotic conversion practice.